Dental microwear texture analysis of Pliocene Suidae from Hadar and Kanapoi in the context of early hominin dietary breadth expansion. Issue 132 (July 2019) - Lazagabaster, Ignacio A.
Abstract: Stable carbon isotope studies suggest that early hominins may have diversified their diet as early as 3.76 Ma. Early Pliocene hominins, including Australopithecus anamensis, had diets that were dominated by C3 resources while Late Pliocene hominins, including Australopithecus afarensis —a putative descendant of A. anamensis —had diets that included both C3 and C4 resources. It has been hypothesized that the expansion of C4 grasslands in eastern Africa during the Pliocene could have prompted hominins to incorporate C4 resources in their diets. However, dental microwear analyses suggest that diet diversification did not involve changes in the mechanical properties of the foods consumed. To provide contextual and comparative information on this issue, the diet of suids from the A. anamensis site of Kanapoi and the A. afarensis site of Hadar is investigated. Using dental microwear texture analyses, it is shown that despite significant dietary overlap, there is evidence for dietary niche partitioning among suids. Based on comparisons with the diet of extant African suids, it is inferred that Nyanzachoerus pattersoni ( n = 21) was a mixed feeder, Nyanzachoerus jaegeri ( n = 4) and Notochoerus euilus ( n = 61) were habitual grazers, and Kolpochoerus afarensis ( n = 34) had a broad diet that included hard brittle foods and underground resources. The dental microwear of Ny. pattersoni and Ny. jaegeri / No. euilus do not differ significantly between Kanapoi and Hadar. Most differences are driven by K. afarensis, a suid absent at Kanapoi but present at Hadar. Food availability probably differed between Hadar and Kanapoi, and it is likely that A. afarensis did not exploit some of the foods (e.g., underground resources) consumed by suids. It is hypothesized that despite the incorporation of C4 resources in the diet, a significant dietary change towards flexible diets in the hominin lineage had yet to come.